RANCANG BANGUN SISTEM PENGOLAHAN SUPPLIER INVOICE ACCOUNTING MENGGUNAKAN METODE EXTREME PROGRAMMING - Agung Triayudi; Vidila Rosalina; Fildzah Fildzah (Universitas Serang Raya, 2014)
The role of information in an organization both private companies and government agencies are very important, because this information can give an idea of the condition or situation of the company. Therefore, the presentation of information needed to be fast, precise and communicative. The results of the analysis of the issues raised in the latest of which is the supplier invoice accounting information received by the management, so that management late in the decision-making. The method used is extreme programming. It is expected that the results of the analysis and design of supplier invoice processing system of accounting is performed in PD. Sampurna Serang, will eventually be able to develop a computer-based information systems to support the handling of various problems in the processing of supplier invoices accounting.